Faktor-Faktor yang Mempengaruhi Minat Siswa SMA/SMK di Magelang dalam Melanjutkan Pendidikan ke Perguruan Tinggi - Irfani, Nafisa Aliya; Maheswari, Nasywa Nathania; Habibie, Renata; Berliana, Elsa Agistina; Lasmini, Ferdita Dewi; Nugraha, Joko Tri (ANTASENA: Governance and Innovation Journal, 2025)
The participation of senior and vocational high school (SMA/SMK) students in pursuing higher education in the Magelang region still shows disparities, despite the availability of various government assistance programs. This phenomenon indicates the presence of specific factors influencing students' decisions to continue their studies. This study aims to identify and analyze the factors that influence the interest of SMA/SMK students in Magelang in pursuing higher education. A descriptive quantitative approach with a correlational design was employed. The sample consisted of 50 twelfth-grade students from five randomly selected schools. The research instrument was a closed-ended questionnaire based on a Likert scale, covering four independent variables: parental support, intrinsic motivation, access to higher education information, and academic readiness. The data were analyzed using descriptive statistics and Pearson correlation tests. The findings reveal that all variables have a positive and significant correlation with students’ interest in pursuing higher education, with intrinsic motivation emerging as the most dominant factor. Parental support—both moral and financial—as well as access to digital information also contributed significantly to shaping students' interests. Academic readiness played an important role in enhancing students’ confidence to continue their studies. This study concludes that students’ interest in pursuing higher education is influenced by the interaction between internal and external factors. Therefore, synergy among schools, families, and the government is needed to strengthen career guidance services and ensure equitable access to information, as strategic efforts to increase higher education participation among SMA/SMK graduates in Magelang.